Cardiac Rehabilitation for Fontan Circulation Patients: A Systematic Review, and Meta-Analysis - Luna van de Ven; Ana Clara Félix; Joana Suarez; Jorge Dias; Fátima F. Pinto; Sérgio Laranjo (Medicina)
Background and Objectives: Despite advances in the surgical management of patients with Fontan circulation, their exercise capacity and quality of life remain significantly impaired. Exercise-based cardiac rehabilitation (CR) offers promising improvements in these areas, but the implementation and adherence to these programmes are often inconsistent. This systematic review and meta-analysis aimed to evaluate the safety, efficacy, and optimal exercise modalities for Fontan patients. Materials and Methods: A systematic search of PubMed, Scopus, Web of Science, and Cochrane Library was conducted on 24 August 2023. Studies were screened and assessed for quality using the Cochrane RoB Tool 2 and STROBE checklist. Meta-analysis was performed using a continuous random-effects model to determine the effectiveness of various CR interventions, including aerobic exercise training (AET), resistance training, and inspiratory muscle training (IMT). Results: A total of 26 studies (7 RCTs, 19 cohorts) comprising 22 distinct cohorts were included, with a total sample size of 428 Fontan patients. The interventions ranged from 4 weeks to 24 months and included AET (18 studies), resistance training (11 studies), and IMT (6 studies). The meta-analysis revealed significant improvements in exercise capacity, with a pooled mean difference in peak VO2 of 1.947 (95% CI: 1.491 to 2.402, p < 0.001). Subgroup analyses showed that combined AET and resistance training had the most robust effect, with a mean difference of 2.11 (95% CI: 1.57 to 2.65, p < 0.001). Home-based interventions showed significant benefits, while supervised and hybrid interventions did not show statistically significant differences. Publication bias was identified, particularly in home-based interventions, where smaller studies demonstrated larger effect sizes, as confirmed by Egger’s test (Intercept = 2.417, 95% CI: 1.498 to 3.337, p = 0.001). However, no significant bias was detected in supervised or hybrid interventions, which displayed symmetrical distributions in funnel plots and non-significant Egger’s test results. Conclusions: CR appears to be an effective intervention for improving exercise capacity in Fontan patients, particularly when combining AET with resistance training. Home-based programmes offer promising results, though the potential for publication bias, especially in smaller studies, warrants cautious interpretation of these findings. Further research is needed to refine protocols, explore long-term outcomes, and determine the underlying mechanisms, particularly for patients with more severe clinical presentations. The low incidence of adverse events across the studies reinforces the safety of these interventions.